Studies on failure behaviour of wire rope used in underground coal mines. (December 2016) - Singh, R.P.; Mallick, Mousumi; Verma, M.K.
Abstract: Wire ropes operate at high stress levels and are almost invariably subject to fluctuating loads. The continuous degradation of wire rope affected with operative services will ultimately lead to failure. Study of the causes of failure of two wire ropes from two different Indian coal mines have been carried out and discussed here. The investigating parameters comprises of physical examination, wear & corrosion, lubrication, macro & micro-examination and chemical composition. The investigation revealed that the major cause of failure was due to excessive wear and corrosion resulted in high reduction in diameter ranging from 50%–90% and poor lubrication condition of wire rope. Micro-examination also revealed intergranular corrosion with cracks and pittings, uniform corrosion with pitting along the grain. Further elongated grain which was indicative of stress due to excessive corrosion with sudden impact resulted in its failure. Highlights: Failed winding rope of 25 mm diameter 6X8FS construction and failed guide rope of 32mm diameter of BCCL, Dhanbad have been studied. The investigation revealed that excessive reduction in wire diameter along with sudden load on wire rope may responsible for its failure. Chemical compositions and poor lubrication are also the factors for the failure because poor lubrication leads to intermittent friction of wires prone to corrosion of the wires.